Lymphocyte HVEM/BTLA co-expression after critical illness demonstrates severity indiscriminate upregulation, impacting critical illness-induced immunosuppression - Wakeley, Michelle E.; Armstead, Brandon E.; Gray, Chyna C.; Tindal, Elizabeth W.; Heffernan, Daithi S.; Chung, Chun-Shiang; Ayala, Alfred (Frontiers in Medicine, 2023)
Introduction The co-regulatory molecule, HVEM, can stimulate or inhibit immune function, but when co-expressed with BTLA, forms an inert complex preventing signaling. Altered HVEM or BTLA expression, separately have been associated with increased nosocomial infections in critical illness. Given that severe injury induces immunosuppression, we hypothesized that varying severity of shock and sepsis in murine models and critically ill patients would induce variable increases in HVEM/BTLA leukocyte co-expression. Methods In this study, varying severities of murine models of critical illness were utilized to explore HVEM+BTLA+ co-expression in the thymic and splenic immune compartments, while circulating blood lymphocytes from critically ill patients were also assessed for HVEM+BTLA+ co-expression. Results Higher severity murine models resulted in minimal change in HVEM+BTLA+ co-expression, while the lower severity model demonstrated increased HVEM+BTLA+ co-expression on thymic and splenic CD4+ lymphocytes and splenic B220+ lymphocytes at the 48-hour time point. Patients demonstrated increased co-expression of HVEM+BTLA+ on CD3+ lymphocytes compared to controls, as well as CD3+Ki67- lymphocytes. Both L-CLP 48hr mice and critically ill patients demonstrated significant increases in TNF-α. Discussion While HVEM increased on leukocytes after critical illness in mice and patients, changes in co-expression did not relate to degree of injury severity of murine model. Rather, co-expression increases were seen at later time points in lower severity models, suggesting this mechanism evolves temporally. Increased co-expression on CD3+ lymphocytes in patients on non-proliferating cells, and associated TNF-α level increases, suggest post-critical illness co-expression does associate with developing immune suppression.